(untitled) (Revista dos Estudantes de Direito da Universidade de Brasília, 2012)
The present article aims to discuss the institute of reservations, by giving a general overview and discussing further the aspect of reservations on human right treaties. Besides that, it analyzes the Brazilian reservation at the Protocol to the American Convention on Human Rights to Abolish the Death Penalty, in this matter, tries to understand the settings that led the country to make such reservation and how it fits in the present environment. After going over some important international documentation, such as United Nations Resolutions and the Rome Statute, it concludes that this specific reservation has become obsolete.